3 - Dimensions of University Governance and Community Relations in Ghana - Akwasi Agyeman, Edmond; Tamanja, Emmanuel M. J.; Bingab, Bernard B. B. (Africa Development, 2021)
community relations among five public universities in Ghana. It focuses on how the universities exercise their corporate social responsibility within the communities where they are located. Place building theory was used for analysis. Key informant interviews were conducted within the research areas. Findings from the study show that there are agitations from the universities’ host communities demanding greater social responsibility and engagement. However, whereas some of the universities have developed an interdependent orientation, others have adopted an independent perspective with respect to their surrounding communities. The article recommends that a multistakeholder approach involving the universities, surrounding communities, government institutions and other third sector organisations is required to address the developmental needs of the communities.